2020
DOI: 10.1680/jwarm.18.00024
|View full text |Cite
|
Sign up to set email alerts
|

MASW survey to estimate the unit weight of municipal solid waste at a landfill in Brazil

Abstract: Non-invasive and non-destructive geophysical methods, such as the multichannel analysis of surface waves (MASW), can effectively provide useful information about the mechanical properties (stiffness and unit weight) of municipal solid waste (MSW), during and after landfill operation, for environmental monitoring and engineering analysis. This paper aims to address the results of a seismic survey performed at a sanitary landfill located 40 km north of Rio de Janeiro, Brazil, to image shear-wave velocity profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Other authors calculated γ from V s using Eq. 1 (Cirone and Park 2020 ) and the correlation developed by Choudhury and Savoikar ( 2009 ) in Eq. 7 (Konstantaki et al 2016 ; Aranda et al 2019 ): …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors calculated γ from V s using Eq. 1 (Cirone and Park 2020 ) and the correlation developed by Choudhury and Savoikar ( 2009 ) in Eq. 7 (Konstantaki et al 2016 ; Aranda et al 2019 ): …”
Section: Resultsmentioning
confidence: 99%
“…Some authors reported increasing V s with depth, suggesting a two-layer division of the waste body (Abreu et al 2016 ; Castelli and Lentini 2017 ; Castelli et al 2017 ; Cirone and Park 2020 ). Higher average velocities in the bottom layer were associated with the increased unit weight ( γ ) of old and deep MSW due to mechanical compression and changes in particle size distribution, mass, and volume during biodegradation.…”
Section: Resultsmentioning
confidence: 99%